Does job opportunities moderate self-confidence and tax knowledge on accounting student interest as tax consultant? - Suyanto; Atikah Nur 'Aini; Fuadhillah Kirana Putri (Jurnal Akademi Akuntansi)
Purpose: The main objective of this study is to investigate how self-confidence and knowledge of taxation impact the accounting students’ interest in pursuing careers as tax consultants and also considering the influence of job opportunities as the moderating factor.